2021
DOI: 10.1002/asjc.2643
|View full text |Cite
|
Sign up to set email alerts
|

Output feedback finite‐time dissipative control for uncertain nonlinear fractional‐order systems

Abstract: This paper solves the robustly finite‐time dissipativity control problems for uncertain nonlinear fractional‐order systems (FOS). Firstly, by using some basic mathematical transformations associated with linear matrix inequality (LMI) techniques, a novel condition for the existence of output feedback controllers is established to ensure the closed‐loop FOS is finite‐time stabilizable. Then, based on the proposed stabilization criterion combined with some well‐known properties of fractional calculus, the finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Finally, pre-multiplying and post-multiplying by diag{I, G} and diag{I, G T }, respectively, and thereby replacing −GP −1 G T with the bounding inequality, −GP −1 G T ≤ −Sym{G} + P [35], one obtains (5). Using similar steps, it can be shown that ( 6) is sufficient for (9). The proof is complete.…”
Section: Proofmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, pre-multiplying and post-multiplying by diag{I, G} and diag{I, G T }, respectively, and thereby replacing −GP −1 G T with the bounding inequality, −GP −1 G T ≤ −Sym{G} + P [35], one obtains (5). Using similar steps, it can be shown that ( 6) is sufficient for (9). The proof is complete.…”
Section: Proofmentioning
confidence: 77%
“…However, this design method becomes tedious with increasing number of state variables, since it involves the dynamics of both the system as well as the observer. Thus, to alleviate this problem, output feedback is generally preferred in many practical applications, for instance, in the works [5][6][7][8][9][10]. With output feedback, only the information of the measurable output is required.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, people are more interested in the transient performance of systems in a finite time, that is, in a limited time interval [21][22][23][24][25][26][27][28][29][30]. Finite-time stability is introduced to deal with these transient performances.…”
Section: Introductionmentioning
confidence: 99%
“…Note that nonlinearity is universal for practical systems. Naturally, fractional-order nonlinear dynamic systems have gained considerable attentions [4][5][6][7][8][9][10]. To name a few, together with neuro-fuzzy network approach, an adaptive output feedback control scheme was proposed in Song et al [7] to handle the tracking problem for the fractional-order systems with unknown nonlinearities.…”
Section: Introductionmentioning
confidence: 99%